The impact of environmental factors on phenotypic diversity of natural populations of Polyspora in China - Ma, Changle; Gong, Maiyu; Gui, Qing; Fan, Zhifeng; Yang, Jianxin; Wang, Lijuan; Deng, Lilan (Frontiers in Plant Science, 2025)
BackgroundPlant phenotypic diversity is not solely determined by genetic variation but is also shaped by the combined effects of environmental factors. Polyspora, a genus within the Theaceae family, consists of evergreen trees or shrubs widely recognized for their horticultural value and suitability for afforestation in mountainous regions. Despite its ecological and economic significance, the genus Polyspora has received relatively limited attention from the plant taxonomy community, and no systematic studies on its phenotypic diversity have been conducted to date.MethodsThus, we conducted a comprehensive investigation on the phenotypic traits of Polyspora (8 species, 32 populations) distributed across China. We employed nested variance analysis to characterize the variation patterns of phenotypic traits within and among populations. Furthermore, redundancy analysis and Pearson correlation analysis were conducted to explore the relationships between leaf morphological traits and geo-environmental variables. A phylogenetic tree was constructed based on 15 morphological traits, and the strength of the phylogenetic signal was quantified using Blomberg’s K statistic.ResultsThe results indicate that the phenotypic traits of Polyspora species exhibit significant interspecific and intraspecific differences, with abundant phenotypic variation. Specifically, the average coefficients of variation (CVs) were 24% for leaf traits, 11.98% for floral traits, and 17.49% for fruit and seed traits. In terms of variation degree, P. longicarpa exhibited the highest variation in leaf traits, P. chrysandra showed the greatest variation in floral traits, and P. axillaris displayed the maximum variation in fruit and seed traits. Among these species, P. speciosa had the largest leaves, whereas P. longicarpa possessed the largest flowers, fruits, and seeds. The 15 morphological traits examined, including style length, sepal length, capsule length, and seed wing length exhibited strong phylogenetic signals (K >>1, P< 0.05). Among the environmental factors analyzed, bioclimatic variables and ultraviolet radiation were found to exert a significant influence on leaf trait variation.ConclusionsThese findings improve our understanding of the morphological characteristics of Polyspora leaves and the extent to which environmental factors drive phenotypic variation. Furthermore, this study provides a scientific basis for the conservation and sustainable utilization of Polyspora resources in future research and practical applications.